A kainate receptor GluK4 deletion, protective against bipolar disorder, is associated with enhanced cognitive performance across diagnoses in the TwinsUK cohort - Koromina, Maria; Flitton, Miles; Mellor, Ian R.; Knight, Helen M. (Taylor & Francis, 2018)
Objectives: Cognitive deficits are a common feature of neuropsychiatric disorders. We investigated the relationship between cognitive performance and a deletion allele within GluK4 protective against risk for bipolar disorder, in 1642 individuals from the TwinsUK study. Methods: Cognitive performance was assessed using the National Adult Reading Test, four CANTAB tests (Spatial Working Memory, Paired Associates Learning, Pattern Recognition Memory, and Reaction Time), and two Principal Component Analysis derived factors. Performance in individuals homozygous for the insertion allele was compared to deletion carriers and analysis was adjusted for age of diagnosis, medication and clinical diagnosis. Results: Individuals with the GluK4 protective deletion allele performed significantly better in Spatial Working Memory compared to insertion homozygotes when adjusted for a clinical diagnosis. GluK4 deletion carriers who had a mental health problem (predominately depression) showed better performance in visuo-spatial ability and mental processing speed compared to individuals with mental health problems homozygous for the insertion. Conclusions: These findings of genotype-dependent cognitive enhancement across clinical groups support the potential clinical use of the GluK4 deletion allele in personalized medicine strategies and provide new insight into the relationship between genetic variation and mood disorders.